J/ψ-hadron correlations at midrapidity in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (Journal of high energy physics, 2025)
We report on the measurement of inclusive, non-prompt, and prompt J/ψ-hadron correlations by the ALICE Collaboration at the CERN Large Hadron Collider in pp collisions at a center-of-mass energy of 13 TeV. The correlations are studied at midrapidity (|y| < 0.9) in the transverse momentum ranges pT < 40 GeV/c for the J/ψ and 0.15 < pT < 10 GeV/c and |η| < 0.9 for the associated hadrons. The measurement is based on minimum bias and high multiplicity data samples corresponding to integrated luminosities of Lint = 34 nb−1 and Lint = 6.9 pb−1, respectively. In addition, two more data samples are employed, requiring, on top of the minimum bias condition, a threshold on the tower energy of E = 4 and 9 GeV in the ALICE electromagnetic calorimeters, which correspond to integrated luminosities of Lint = 0.9 pb−1 and Lint = 8.4 pb−1, respectively. The azimuthally integrated near and away side yields of associated charged hadrons per J/ψ trigger are presented as a function of the J/ψ and associated hadron transverse momentum. The measurements are discussed in comparison to PYTHIA calculations.